Assessment of demographic factors and mental health status: initiating a healthy campus program - Djannah, Sitti Nur; Trisnowati, Heni; Andriyani, Andriyani; Akmal, Akmal; Tino, Marilou D.; Briones, Jane T.; Siswanto, Deny Hadi (International Journal of Public Health Science (IJPHS), 2024)
Mental health issues have been essential in formulating global health policies for 30 years. The campus community is inseparable from the problem of mental health disorders, which can affect the work either students, lecturers, or staff. This research aimed to describe mental health conditions among the campus community based on demographic factors as an opportunity to initiate a healthy campus program. This study used a quantitative method with a cross-sectional design. The population was an academic community at a private campus in Yogyakarta, Indonesia. There are 347 samples taken by accidental sampling. The mental health instrument used the self-reporting questionnaire. There, 60.81% of respondents experienced psychological disorders, and 73.49% of respondents needed to be referred to a mental health professional regarding addiction, psychotic disorders, and post-traumatic stress disorder (PTSD). There was a significant relationship between demographic factors consisting of gender, age, type of work, employment status, education level, faculty, and emotional disorders with a p-value of <0.005. Moreover, age, gender, education level, type of work, and employment status related to mental disorders due to addiction, psychosis, and PTSD with a p-value<0.005. It is concluded that a large proportion of responders need a referral to a mental health expert. To promote a healthy campus, university officials should follow up with health promotion initiatives such as partnering with the local health office and public health center for additional treatment and improving policy support.